GAMBARAN PENGETAHUAN MASYARAKAT DALAM PEMANFAATAN POSYANDU DI DESA MARGO MULYO KABUPATEN BENGKULU TENGAH, AGUSTUS 2017 - Halinti, Yatri (Journal Of Midwifery, 2018)
Posyandu services are very important for the health of mothers and toddlers but in reality, many people still do not take advantage of posyandu program, it can be seen from the number of attainment of complete basic immunization indicator in toddlers. Where the achievement of this indicator in Indonesia in 2015 amounted to 86.54%. This figure has not reached the Renstra target of 91%. Many factors that can influence the behavior of the community in using posyandu are public knowledge about the utilization of posyandu. This research aimed to determine the description of public knowledge in the utilization of posyandu in Margo Mulyo Village, Central Bengkulu District, August 2017. The research method used is a descriptive research, with the number of samples of 64 respondents taken by accidental sampling technique. The type of data used in this research was using primary data which was analyzed using univariate analysis. The results of this research can be concluded that more than some respondents 37 (57.8%), had less knowledge about posyandu utilization. To the village of Margo Mulyo, Central Bengkulu Regency is expected to be able to cooperate with the health centers and health institutions to provide information to the community, especially pregnant women and mothers who have a toddler.